Mordecai's royal vestments princely and/or priestly? - Spoelstra, Joshua Joel (2019)
This essay examines the function of clothing and related accoutrements in the book of Esther. The motif of dressing and undressing oneself or another signals a shift in the investment or divestment of power and status. Identity, agency, and authority are also signified by vestments and appurtenances. Through synchronic and diachronic exegetical methodologies, Mordecai's regalia of Esth 8:15 is the focus of this essay. This regalia evokes both princely and priestly ideology; therefore, the regalia is a significant symbol for the diasporic, post-monarchic Jewish people in the Persian period. The closest post-exilic analogue to Mordecai's royal vestments and accessories is the diarchic portending prophecies of Zech 6; thus, extrapolations are made accordingly. Ultimately, a definite determination of the significance of Mordecai's regalia cannot be made; nevertheless, the royal vestments are likely imbued with a complex intention-to ignite the imagination of the possibilities for the Jewish people's open-ended future.